Preventable fractions of colon and breast cancers by increasing physical activity in Brazil: perspectives from plausible counterfactual scenarios - Rezende, Leandro Fórnias Machado de (Cancer Epidemiol, 2018)
BACKGROUND: Physical activity is associated with lower risk of colon and breast cancers. Herein we estimated preventable fractions of colon and breast cancers in Brazil by increasing population-wide physical activity to different counterfactual scenarios. METHODS: We used data from a representative national survey in Brazil and corresponding relative risks of colon and postmenopausal breast cancers from a meta-analysis. Estimated cancer incidence was retrieved from GLOBOCAN and Brazilian National Cancer Institute. Five counterfactual scenarios for physical activity were considered: (i) theoretical minimum risk exposure level (≥8,000 metabolic equivalent of tasks-minute/week – MET-min/week); (ii) physical activity recommendation (≥600 MET-min/week); (iii) a 10% reduction in prevalence of insufficient physical inactivity (<600 MET-min/week); (iv) physical activity level in each state equals the most active state in Brazil; (v) closing the gender differences in physical activity. RESULTS: About 19% (3,630 cases) of colon cancers and 12% (6,712 cases) of postmenopausal breast cancers could be prevented by increasing physical activity to ≥8,000 MET-min/week. Plausible counterfactual scenarios suggested the following impact on cancer prevention: reaching physical activity recommendation: 1.7% (1,113 cases) of breast and 6% (1,137 cases) of colon; 10% reduction in physical inactivity prevalence: 0.2% (111 cases) of breast and 0.6% (114 cases) of colon; most active state scenario: 0.3% (168 cases) of breast and 1% (189 cases) of colon; reducing gender differences in physical activity: 1.1% (384 cases) of breast and 0.6% (122 cases) of colon. CONCLUSIONS: High levels of physical activity are required to achieve a sizable impact on breast and colon cancer prevention in Brazil.